The dangers of Christian practice: on wayward gifts, characteristic damage, and sin - Winner, Lauren F. (Yale University Press, 2018)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Characteristic Damage -- Eucharist -- Prayer -- Baptism -- Damaged Gifts -- Appendix: Depristinating Practices -- Notes -- Works Cited -- Acknowledgments -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- V -- W -- Z